rdlc 2020
DOI: 10.7764/rdlc.19.3.347-357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasticizer and antifreeze on concrete at elevated temperatures and different cooling regimes

Abstract: In recent years, chemical admixtures have become one of the main components of concrete alongside aggregate, cement and water. In this study, the plasticizer and the antifreeze were used. The concrete specimens (the reference concrete without an admixture, concrete with plasticizer, concrete with antifreeze and concrete with plasticizer+antifreeze) were exposed to elevated temperatures (200, 400, 550 and 700 ºC) and cooling via air and water. Water absorption, ultrasonic pulse velocity and compressive strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…These conditions menti in the literature can explain the significant decrease in UPV values observed for sam exposed to temperatures of 600 and 800 °C. Overall, the UPV findings for samples co in air and water are consistent with the findings of previous literature studies [50,51] ditionally, it has been reported that UPV results are related to pore structure and sa…”
Section: Comparison Of Upv Findings For Samples Cooled In Air and Watersupporting
confidence: 91%
See 2 more Smart Citations
“…These conditions menti in the literature can explain the significant decrease in UPV values observed for sam exposed to temperatures of 600 and 800 °C. Overall, the UPV findings for samples co in air and water are consistent with the findings of previous literature studies [50,51] ditionally, it has been reported that UPV results are related to pore structure and sa…”
Section: Comparison Of Upv Findings For Samples Cooled In Air and Watersupporting
confidence: 91%
“…Topcu and Demir [49] have also reported that the breakdown of the C-S-H gel at temperatures above 450 • C reduces the speed of sound wave propagation and hence decreases UPV values. These conditions mentioned in the literature can explain the significant decrease in UPV values observed for samples exposed to temperatures of 600 and 800 • C. Overall, the UPV findings for samples cooled in air and water are consistent with the findings of previous literature studies [50,51]. Additionally, it has been reported that UPV results are related to pore structure and sample density and that there is a relationship between mechanical properties and UPV results [17,52].…”
Section: Comparison Of Upv Findings For Samples Cooled In Air and Watersupporting
confidence: 90%
See 1 more Smart Citation
“…There are various types of cooling, such as air and water. Kara and Arslan [42] investigated the high-temperature effect of plasticizer and antifreeze additives on cementitious composites. They found that the decrease in strength was the highest in the mixtures where plasticizer and antifreeze were used together for both cooling types at temperatures of 550 • C and 700 • C. In contrast, the lowest strength decrease was obtained from the samples with antifreeze added to the water cooler.…”
Section: Introductionmentioning
confidence: 99%